2021
DOI: 10.1038/s41467-021-26331-7
|View full text |Cite
|
Sign up to set email alerts
|

GAK and PRKCD are positive regulators of PRKN-independent mitophagy

Abstract: The mechanisms involved in programmed or damage-induced removal of mitochondria by mitophagy remains elusive. Here, we have screened for regulators of PRKN-independent mitophagy using an siRNA library targeting 197 proteins containing lipid interacting domains. We identify Cyclin G-associated kinase (GAK) and Protein Kinase C Delta (PRKCD) as regulators of PRKN-independent mitophagy, with both being dispensable for PRKN-dependent mitophagy and starvation-induced autophagy. We demonstrate that the kinase activi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 73 publications
5
27
1
Order By: Relevance
“…A clear contrast between our results and the published literature on iron depletion is timing, as most studies have focused predominantly on signalling events following 18–24 h of chelation treatment (Oexle et al , 1999 ; Allen et al , 2013 ; Hara et al , 2020 ; Zhao et al , 2020 ; Munson et al , 2021 ). Specifically, temporal metabolomics revealed that iron depletion is a potent signal that induces alterations in cellular lipid recomposition within minutes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A clear contrast between our results and the published literature on iron depletion is timing, as most studies have focused predominantly on signalling events following 18–24 h of chelation treatment (Oexle et al , 1999 ; Allen et al , 2013 ; Hara et al , 2020 ; Zhao et al , 2020 ; Munson et al , 2021 ). Specifically, temporal metabolomics revealed that iron depletion is a potent signal that induces alterations in cellular lipid recomposition within minutes.…”
Section: Discussioncontrasting
confidence: 99%
“…Lysosomes appeared to retain their overall acidity upon DGAT1/2 inhibition, but whether fusion dynamics, trafficking or autophagosome‐lysosome reformation might be affected is unclear. In agreement with our discovery that lipid homeostasis modifies mitophagy, a recent study reported a role for two lipid‐binding kinases (GAK and PRKCD) in Parkin‐independent mitophagy, and their inactivation induced endolysosomal dysfunction independently of effects on acidity (Munson et al , 2021 ). Of interest, the accumulation of mitochondrial DAG is hypothesised to play a role here, which is related to oxidative stress (Cowell et al, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Given the membrane dependence of the autophagy pathway, we focused specifically on proteins that contain domains known to interact with lipids (e.g., FYVE, PX, C1, C2 domains, etc.). Carrying out an image-based siRNA screen in U2OS cells expressing a mitochondrial matrix localized EGFP-mCherry reporter, we determined that the kinases GAK (cyclin G associated kinase) and PRKCD (protein kinase C delta) act as positive regulators of DFP-induced mitophagy [ 1 ]. We validated their effect on mitophagy through several means, including biochemical activity assays, Western blot, and proteomic-based approaches.…”
mentioning
confidence: 99%